Effects Of Current Density, Etching Time And Hydrofluoric Acid Concentration On The Formation And Morphology Of Highly Doped N-Type Porous Silicon - Yaakob, Suriani Haji (2011)
Highly doped n-type porous silicons (PS) were prepared via electrochemical etching. The effect of current density (50 – 300 mA cm-2), etching time (30 – 300 s) and HF concentration (9.2 – 49.0% (v/v)) on the morphology, pore diameter, porosity, surface roughness and electrical properties of the PS were studied. These properties were characterized by Scanning Electron Microscopy (SEM), gravimetric method, Atomic Force Microscopy (AFM) and Current-Voltage (I-V) characteristics. The increment in current density has changed the morphology of the PS from interconnected network to columnar with side branching. However, with the increase in the etching time and HF concentration, this disappeared to give smooth side wall pores.